Violence in sports: A look at mental endurance, problem-solving, and violent tendencies in young active athletes - Kara, Tayfun (SPORT TK-EuroAmerican Journal of Sport Sciences, 2025)
This study aimed to examine the relationship between mental endurance, problem-solving skills, and attitudes toward violence in sports among young active athletes. The study population consisted of individuals aged 15–35 residing in Ankara Province, and the sample included 101 volunteer athletes training in various sports branches at the Youth and Sports Club in the Etimesgut district. Data were collected using a demographic information form, the Mental Endurance Inventory, the Independent–Reciprocal Problem-Solving Scale, and semi-structured interviews. The quantitative data were analyzed using SPSS (v. 22.0), while the qualitative data were evaluated through thematic analysis. The findings indicated that the athletes generally demonstrated above-average levels of mental endurance and problem-solving skills, while their tendencies toward violence were relatively low. Moreover, athletes who scored higher in the sub-dimensions of emotional control and stress management were better able to regulate negative emotions such as anger during competition and were less prone to aggressive behavior. Our findings highlight the crucial role of psychological resilience and social support in preventing violence in sports. Therefore, investing in the mental and social development of young athletes—by all stakeholders, including coaches, sports psychologists, families, and sports administrators—appears to be one of the most effective strategies to combat violence in the sporting arena.